COMPETENCY DEVELOPMENT VALIDITCERTIFICATION IN TEST MODELING AND WEB PROGRAMMING IN VOCATIONAL EDUCATION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Abstract. The purpose of this study is to assess the product validation of competency test model development and web programming certification in vocational education. The steps of the borg and gall model are used in this study. Experts in the field of learning models, evaluation experts, competency experts, media experts, and linguists evaluated the model validation test. Validation sheets in the form of model books, teaching modules, applications, assessor guidebooks, and participant guidebooks are used to measure the model's validity. The data analysis technique employs Aiken V validation testing to determine whether or not the developed model is declared valid. The development of a competency test model and web programming certification in vocational education that produces products in the form of model books, teaching modules, applications, assessor guidebooks, and participant guidebooks is declared valid based on the validation results.